Rebuilding multilateralism : the key for global peace and development - Patterson, P. J. (Jamaica Information Service KingstonJM, 2003)
Notes the need for UN reforms and looks at international issues. Highlights the international economy and the need for cooperation for development. Focuses on trade development and globalization.